Motion of charged particles around a five-dimensional rotating magnetized black hole - Kaya, R. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
We study the effect of an external magnetic field on the stability of circular motion of charged particles in the equatorial plane of a five-dimensional rotating black hole. Using the Hamilton-Jacobi formalism, we derive the effective potential for the radial motion of test particles around a five-dimensional magnetized Myers-Perry black hole. We show that there exist stable circular orbits in equatorial planes in the background of this metric.
Keywords: gravity in more than four dimensions; classical black holes; FIELD; EQUATIONS; ENERGY; Astronomy & Astrophysics